JAMUR ENTOMOPATOGEN DAN AKTIVITAS ENZIM EKSTRASELULERNYA - Suciatmih, Suciatmih; Kartika, Titik; Yusuf, Sulaeman (Research Center for Biology-Indonesian Institute of Sciences, 2015)
Isolation of entomopathogenic fungi and their extracellular enzyme activity from rhizosphere soil were carried out. Soil samples were collected from rhizosphere under Arecaceae plant collection and a shrub in Bogor Botanic Garden, West Java; and another samples were gathered from forest floor on peat land in Sebangau National Park, Central Kalimantan. Insect bait method was used to catch fungi from soil samples by using Coptotermes sp. termites and Xystrocera festiva larva in the laboratory. A total of 38 fungal isolates belonging to 18 species and 12 genera were successfully isolated and identified. Isolated fungi were dominated by Deuteromycotina; and Fusarium is the most common (5 species). Peat and Pinanga coronata rhizospheres; and termites bait gave the highest fungal diversity of 9 species respectively. All fungal isolates did not indicate chitinase activity, but 60.53 %, 10.53 % and 13.16 % had both of lipase and protease; lipase and protease activities, respectively. Only 15.79 % fungal isolates were negatively in lipase or protease activities.